A Legal Analysis of Self-Defense (Noodweer) in Criminal Assault Cases - Alfredo Rynaldi; Hadina Rivaldi Diaz; Angga Hendrawinangun (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
The application of self-defense (noodweer) in assault cases remains a controversial issue in Indonesian criminal law, particularly regarding the limits of justified defensive actions and criminal liability in spontaneous multi-party conflicts. This study aims to analyze the criminal liability of the parties involved and examine the applicability of noodweer and noodweer exces under the Indonesian Criminal Code. This research employs a normative juridical method using statutory and conceptual approaches. Primary legal materials consist of Articles 49 and 351 of the Indonesian Criminal Code, supported by secondary legal materials, including legal doctrines, scholarly literature, and recent studies. The collected legal materials were analyzed qualitatively through descriptive-analytical methods. The findings indicate that A acted as the initial aggressor by initiating and continuing unlawful violence against B and C. Although B's act of striking A with a wooden object formally fulfills the elements of assault, it may be justified as noodweer or alternatively categorized as noodweer exces. Meanwhile, C's intervention is solely aimed at preventing further violence and therefore does not constitute a criminal offense. The study emphasizes the importance of contextual interpretation, proportionality, and defense of others in determining criminal liability.